Blast Protection of Buildings. - Engineers, American Society of Civil (Reston : American Society of Civil Engineers, 2023)
Standard ASCE/SEI 59-22 provides minimum requirements for planning, design, construction, and assessment of new and existing buildings subject to the effects of accidental or malicious explosions.
10.1 SCOPE.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books